Association of Sirtuin 1 rs7069102 Gene Polymorphism with The Risk of Diabetic Nephropathy in Egyptian Patients (International Journal of Environmental Sciences, 2025)
Background: Diabetes is a heterogeneous complex metabolic disease marked by raised concentration of blood glucose due to either insulin resistance, inadequate production of insulin, or both.Aim: To examine the association between SIRT1 rs7069102 polymorphism and diabetic nephropathy (DN) in Egyptian cases who have type 2 diabetes mellitus (T2DM).Patients and methods: This case–control research has been performed on 90 individuals: 30 cases with DM type II with diabetic nephropathy [albumin-to-creatinine ratio (ACR) above 30 milligrams per gram], 30 patients with DM type II without DN (ACR under 30 milligrams per gram), and 30 apparently healthy individuals of matched sex and age selected as a control group. Cases were selected from the clinics of the internal medicine department, Beni-Suef University Hospital.Results: The risk of acquisition of diabetic nephropathy (compared with diabetes without nephropathy) was increased by the presence of CC 3.14 times, and the probability of risk of DN decreased by the presence of CG 0.23 times. The GG genotype expression didn’t differ significantly between DM and DN. A statistically significant variance has been observed between the three groups with regard to the SIRT1 rs7069102 polymorphism.Conclusion: The current research illustrated that a significant correlation has been observed between Sirtuin 1 rs7069102 polymorphism and the possibility of developing diabetic nephropathy in Egyptian cases. CC genotype and C allele have been related to an elevated possibility of developing DN.